2023
DOI: 10.1111/liv.15730
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study on the prevalence of MASLD in people with type‐2 diabetes in the community. Cost effectiveness of screening strategies

Roberta Forlano,
Tijana Stanic,
Sahan Jayawardana
et al.

Abstract: Background and AimsAs screening for the liver disease and risk‐stratification pathways are not established in patients with type‐2 diabetes mellitus (T2DM), we evaluated the diagnostic performance and the cost‐utility of different screening strategies for MASLD in the community.MethodsConsecutive patients with T2DM from primary care underwent screening for liver diseases, ultrasound, ELF score and transient elastography (TE). Five strategies were compared to the standard of care: ultrasound plus abnormal liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The predominant cardiovascular risk factor of MASLD is BMI > 23 kg/m 2 [17] . T2DM is an independent predictor of MASLD and its complications, especially if associated with tobacco consumption [50,51] . In this context, several classes of antidiabetic drugs have favorable effects on liver function [52] .…”
Section: Cardiovascular and Metabolic Featuresmentioning
confidence: 99%
“…The predominant cardiovascular risk factor of MASLD is BMI > 23 kg/m 2 [17] . T2DM is an independent predictor of MASLD and its complications, especially if associated with tobacco consumption [50,51] . In this context, several classes of antidiabetic drugs have favorable effects on liver function [52] .…”
Section: Cardiovascular and Metabolic Featuresmentioning
confidence: 99%
“…MASLD is widely recognized as the most prevalent chronic liver disease, which affects around 30% of the global population (2). The prevalence of MASLD in type 2 diabetes patients is approximately 65% (3). Additionally, previous researches have demonstrated that the prevalence of MASLD shows a remarkable sex disparity, with higher risk among men (4).…”
Section: Introductionmentioning
confidence: 97%
“…Increasing researches have demonstrated that MASLD is linked with multiple metabolic disorders, including insulin resistance, obesity and abnormal glucose metabolism (29). MASLD and type 2 diabetes frequently occur together (3). Therefore, our study was to explore the relation between peripheral NLR values and MASLD in Chinese type 2 diabetes patients.…”
Section: Introductionmentioning
confidence: 98%
“…T2DM patients represent an important target group for the detection of MASLD, which can even progress to liver fibrosis with the development of more severe comorbidities. In both conditions, a possible key factor could be the presence of insulin resistance (IR) and adipose tissue disorders that are linked to the pathophysiology of “metabolic dysfunction,” liver disease, and the development of cardiovascular and metabolic complications [ 7 ].…”
Section: Introductionmentioning
confidence: 99%